AB0509 Kzr-616, a selective inhibitor of the immunoproteasome, shows a promising safety and target inhibition profile in a phase i, double-blind, single (SAD) and multiple ascending dose (MAD) study in healthy volunteers. (12th June 2018) - Lickliter, J.; Bomba, D.; Anderl, J.; Fan, A.; Kirk, C.J.; Wang, J.
Abstract : Background: Proteasome inhibition is a standard of care for plasma cell malignancies. Bortezomib targets the constitutive proteasome and immunoproteasome, and is effective in the treatment of Systemic Lupus Erythematosus (SLE) and lupus nephritis (LN), but is associated with hematologic (e.g. thrombocytopenia) and constitutional (e.g. peripheral neuropathy) adverse events (AEs). Objectives: We report the safety, pharmacokinetics (PK), pharmacodynamics (PD) and immunomodulatory effects of KZR-616, a first-in-class selective inhibitor of the immunoproteasome, in healthy volunteers (HV) following single and repeat subcutaneous (SC) administration. Methods: Cohorts (6 drug:2 placebo) received single or 4 weekly SC doses. Safety assessments, PK and PD were measured to Day 7 (SAD) or Day 28 (MAD). SAD cohorts included 7.5, 15, 30 and 60 mg (SC). MAD cohorts included 30, 45, 60 mg, and 2 intrasubject escalation cohorts with 1 dose at 30 mg and 3 doses at 45 mg. PK was measured by LC/MS 2 . PD was measured using enzymatic and active site binding assays. Inflammatory cytokine release was measured following ex vivo stimulation of whole blood in HV receiving placebo or 45 mg KZR-616. Results: 32 HV (24:8) were enrolled in 4 SAD cohorts. The most common AEs were injection site reactions (ISRs), which were generally mild and transient. No clinically-significant (CS) laboratory or ECG abnormalities and no dose limiting toxicities were observed in the SAD subjects. Following SC administration, drug exposure increased dose proportionally and was characterised by rapid absorption (Tmax 15–30 min) and clearance (T1/2 ~2 hours). Inhibition of the immunoproteasome exceeded 80% at ≥30 mg with significant recovery noted over 7 days. Constitutive proteasome inhibition was <37% in all cohorts. 40 HV (30:10) were enrolled in 5 SC MAD cohorts. In the initial cohort of 60 mg, a systemic drug reaction (chills, elevated heart rate, nausea) occurred ~8 hours after the first dose in 4 subjects. Dosing for this cohort was stopped. Subsequent cohorts (initiated at 30 mg) received prophylactic treatment with antihistamines±prednisone 1 hour prior to the first and second dose. No similar AEs occurred with repeat dosing of 45 mg. No CS laboratory or ECG abnormalities were seen in the remaining MAD cohorts. ISRs did not appear to increase in severity or frequency with repeat dosing. There were no AEs of peripheral neuropathy, and 45 mg was well tolerated across 3 cohorts. Consistent PK was noted following repeat administration and no drug accumulation was observed. At 45 mg, inhibition of 2 key subunits of the immunoproteasome, LMP7 and LMP2, was ~95% and~70%, respectively. Reduced ex vivo stimulated production of multiple cytokines (IL-23, IL-6, TNF-a, IL-17) was noted in subjects receiving repeat administration of 45 mg KZR-616. Conclusions: KZR-616 up to 45 mg was well tolerated in HV and demonstrated consistent PK and PD. Selective immunoproteasome inhibition did not induce hematologic or constitutional toxicities associated with bortezomib. Candidate dose levels were identified to explore safety, tolerability and efficacy in patients with SLE and LN in an ongoing Phase 1b/2 study. Disclosure of Interest: J. Lickliter: None declared, D. Bomba Employee of: Kezar Life Sciences, J. Anderl: None declared, A. Fan: None declared, C. Kirk: None declared, J. Wang: None declared